From Residential Facilities to Supported Housing: The Personal Health Budget Model as a Form of Coproduction. Issue 1 (2nd January 2016) - Ridente, Pina; Mezzina, Roberto
Abstract: During the deinstitutionalization process in Trieste, an array of different residential facilities were identified and used for different purposes in the course of time. They were integrated in the Mental Health Department and operated in close connection with 24-hour Community Mental Health Centres. Over the last decade, a steady decline in residential beds was achieved also thanks to the implementation of a health budget model in connection with a bespoke therapeutic rehabilitation program. The whole process was focused on reorganizing and transforming existing facilities and organizations to bring them closer to personal needs. Supported housing can be relevant to a recovery process, while the individual health budget has proven to be a crucial design tool shared by users and nonprofit organizations to engage community resources and services and enhance the social capital of people. Empirical data on personalized care projects for people with complex needs show the reconversion of resources from facilities to living environments and social networks, as well as a number of impacts on the overall system, which indicate a true process of coproduction.